Fasting blood glucose, blood pressure and body mass index among combined oral contraceptive users in Chencha town Southern Ethiopia, 2019 - Kofole, Zelalem; Haile, Diresbachew; Solomon, Yerukneh (Frontiers in Global Women's Health, 2023)
Background: The use of contraceptives has become prevalent among women in Ethiopia. Oral contraceptive use has been suggested to trigger changes in glucose metabolism, energy expenditure, blood pressure, and body weight, among various populations and ethnic groups. Objective: To elucidate the pattern of fasting blood glucose, blood pressure, and body mass index among combined oral contraceptive pills users compared to controls. Methods: An institution-based cross-sectional study design was employed. A total of 110 healthy women using combined oral contraceptive pills were recruited as cases. Another 110 healthy age and sex-matched women not using any hormonal contraceptives were recruited as controls. A study was conducted between October 2018 and January 2019. Data obtained were entered and analyzed using IBM SPSS version 23 software packages. One-way ANOVA was used to identify the variation of variables in relation to the duration of use of the drug. The P-value of < 0.05 at the 95% confidence level was statistically significant. Results: Fasting blood glucose level among oral contraceptive users was significantly different differs by 2.9% when compared to control groups with mean values (88.55 ± 7.89 mg/dl vs. 86.00 ± 9.85 mg/dl) among users and controls respectively, P = 0.025). There was a significant difference in the mean arterial pressure of users compared to controls with mean values (88.2 ± 8.48 mmHg vs. 86.0 ± 6.74 mmHg respectively, P=0.04). The mean weight and body mass index of users were significantly different from non-users (P = 0.03 and P = 0.003), respectively. Differences in mean fasting blood glucose level and mean weight of users were independent (P = 0.27 and P = 0.46) of the duration of using oral contraceptives. On the other hand, the mean body mass index and mean arterial pressure of oral contraceptive users were dependent on the duration of use (P < 0.05 and P < 0.001) respectively. Conclusions: Combined oral contraceptives appear to cause a 2.9% difference in fasting blood glucose level, 2.5% in mean arterial pressure, and 3.9% in body mass index among the users.